Spatial Distribution of Agricultural Sector Key to Bengkulu Province's Economic - Mujiono Mujiono; Rinto Noviantoro; Eko Sumartono; Ana Nurmalia (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Input Output (I-O) analysis is an analysis commonly used to analyze and find out the leading sectors in region. However, I-O analysis alone cannot say where the sector / industry base is located spatially and its distribution. Location Quotient (LQ) analysis is conducted to answer this question. The result of the combination of the two shows that the agricultural sector is still the leading sector for the economy of Bengkulu Province. While the agricultural base is found in five districts, including; Lebong Regency, Kepahiang Regency, Kaur Regency, Seluma Regency, and Muko-muko Regency. Overall, the agricultural sector in Bengkulu Province is still a key economic sector, so the development of the agricultural sector as a whole has the potential to have a big effect on the economy of Bengkulu Province itself.